Fast multi-residue method for determination of nineteen benzimidimidazoles in meat tissues by liquid chromatography tandem mass spectrometry - Milena Funeva-Peycheva; Georgi Stoev (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2019)
A fast, sensitive and selective method has been developed for quantitative determination of residues of nineteen benzimidazoles in meat by speeding the productivity of the conventional liquid chromatographs. The analytes are extracted with phosphate buffer and acetonitrile. Extract is purifi ed by Strata X cartridges. Benzimidazoles are separated within 9 min with a conventional liquid chromatograph. The residues are detected by mass spectrometry at Selected Reaction Monitoring SRM.